Implementation of the Occupational Health and Safety Management System at Hard Rock Hotel Bali, Kuta, Bali - Labindao, I Gede Jesika; Sri, Anak Agung Putri; Sari, Ni Putu Ratna (Jurnal Kepariwisataan dan Hospitalitas, 2019)
Abstract The Occupational Health and Safety Management System is part of the overall management system of the company in order to control risks related to work activities in order to create an efficient, safe and productive workplace. There are several work accidents at Hard Rock Hotel Bali such as the occurrence of employees who are exposed to electricity when working and employees who are exposed to broken glass when doing work. Because this is the background of this research. The purpose of the research is to know and understand the application of occupational health and safety management systems and to find out the responses of employees to occuoatinal health and safety management systems in Hard Rock Hotel Bali. This research is located at Hard Rock Hotel Bali. Data collection through observation, interviews, questionnaires and literature studies. Questionnaires were distributed to 120 respondents who were employees of Hard Rock Hotel Bali using proportional stratified sampling technique by determining sampling by lottery. The analysis technique uses qualitative descriptive, validity test,reliabilty test and skala likert. The implementation of the Occupational Health and Safety Management System at Hard Rock Hotel Bali has been carried out in accordance with government regulations No. 50 of 2012 concerning Occupational Health and Safety Management Systems. There are several indicators that have not been optimally applied, including initial reviews and work safety and implementation indicators. The results of employee perceptions of the Occupational Health and Safety System Implementation at Hard Rock Hotel Bali have been carried out well with the percentage of employee perceptions of policy and planning totaling 3.21 with agreed categories, employee perceptions of implementation amounting to 3.24 with agreed categories and employee perceptions towards evaluation and review totaling 3.26 with strongly agreed categories, the overall results of employee perceptions of the Occupational Health and Safety Management System Implementation at Hard Rock Hotel Bali were 3.23 with agreed categories. KeyWord                               : Management System, Implementation, Hard Rock Hotel                                                                       Bali